Development dynamics of port-cities interface in the Arab Middle Eastern world - The case of Dubai global hub port-city - Akhavan, Mina (Cities, 2017)
Many scholars in the field of architecture, urban planning, transportation, geography, economics and sociology have studied port-cities from different perspectives. Yet, the majority of literature on this topic is concerned about the Developed Western and East Asian World. With the aim to contribute to the existing studies and to fill this gap in the literature, this paper makes an attempt to study an example in the fast-developing Arab States in the Middle East, which has recently drawn a particular attention among the scholars. Dubai provides an interesting case study, as it currently hosts the major transhipment hubport of the region. Centred on a single case-study approach, a four-phase model is hypothesized as a tool to investigate the changing spatial and functional dynamics at the port-city interface from the 1900s to the 2010s. The argument is based on a reciprocal relationship between the port and the city, since the advent of a free port. Historically the port has been the economic backbone. Consequently the Creek dredging and newly constructed ports integrated with ancillary infrastructures (such as FTZs) have played an important role in boosting the growth. Some concluding remarks underline the main trends in Dubai's port-city development, compared to the existing European and Asian models. This dynamic evolution is influenced by internal factors, such as oil revenues and governmental strategies, as well as external ones, like the regional and global forces. Despite sharing common features with the Asian consolidation model, this study suggests that Dubai may demonstrate a particular pattern of port-city development.